Orthopedic wear debris mediated inflammatory osteolysis is mediated in part by NALP3 inflammasome activation. Issue 1 (29th August 2012) - Burton, Lyndsey; Paget, Daniel; Binder, Nikolaus B.; Bohnert, Krista; Nestor, Bryan J.; Sculco, Thomas P.; Santambrogio, Laura; Ross, F. Patrick; Goldring, Steven R.; Purdue, P. Edward
Abstract Activation of myeloid cells by orthopedic particulate debris is a key event in the pathogenesis of periprosthetic osteolysis and implant loosening after total joint replacement (TJR). Several lines of evidence implicate NACHT, LRR, and PYD domains‐containing protein 3 (NALP3) inflammasome‐mediated production of interleukin 1 beta (IL‐1β) in the pathogenesis of clinical disorders ascribable to foreign particulate materials, including asbestos, silica, and urate crystals. Recent reports indicate that orthopedic polymer products and metallic particulates and ions may activate the same pathway. Here, we investigated the contribution of the NALP3 inflammasome to the pathogenesis of peri‐implant osteolysis. Pharmaceutical and genetic perturbations of caspase‐1 and inflammasome components were used to assess the role of the NALP3 inflammasome in IL‐1β production and osteoclast formation by human monocytes and mouse macrophages in response to polymethylmethacrylate (PMMA) particle phagocytosis. The role of caspase‐1 in a mouse calvarial model of particle‐mediated osteolysis was assessed using µCT. Phagocytosis of PMMA particles induces caspase‐1 dependent release of IL‐1β from human monocytes and mouse macrophages. Importantly, using macrophages from mice deficient in components of the NALP3 inflammasome, we show PMMA‐induced IL‐1β production is strictly dependent on these components. Mice lacking caspase‐1, the sole effector of the NALP3 inflammasome, show reduced orthopedic wear particle‐induced calvarial osteolysis compared to wild‐type controls. Absence of NALP3 inflammasome components fails to alter osteoclast formation in vitro. Our findings identify the NALP3 inflammasome as a critical mediator of orthopedic wear‐induced osteolysis and as a viable therapeutic target for the treatment of periprosthetic osteolysis. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31:73–80, 2012